Continuous maps preserving Jordan triple products from 𝔾𝕃1 to 𝔾𝕃2 and 𝔾𝕃3. Issue 2 (25th January 2021) - Taghavi, Ali; Salehi, Sadegh
Abstract : Let G L n be a complex general linear group. In this paper we determine the structure of all Jordan triple product maps from G L 1 to G L m for m = 2, 3 . The results are applied to determine the structure of all continuous Jordan triple product maps between G L 1 and G L m for m = 2, 3 . These are the continuous maps ϕ : G L 1 → G L m which satisfy ϕ ( z w z ) = ϕ ( z ) ϕ ( w ) ϕ ( z ), z, w ∈ G L 1 .